Moral Intensity, Issue Importance, and Ethical Reasoning in Operations Situations - Valentine, Sean (Journal of business ethics, 2012)
Previous work suggests that moral intensity and the perceived importance of an ethical issue can influence individual ethical decision making. However, prior research has not explored how the various dimensions of moral intensity might differentially affect PIE, or how moral intensity might function together with (or in the presence of) PIE to influence ethical decision making. In addition, prior work has also not adequately investigated how the operational context of an organization, which may embody conditions or practices that create barriers to ethical decision making, may differ from other functional areas of an organization. Consequently, this study investigated the relationships among moral intensity, perceived ethical issue importance, and three stages of the ethical reasoning process: recognition of an ethical issue, ethical judgment, and ethical intention. Using an internet-based, self-report survey containing two operations management scenarios and various ethics measures, information was collected from business professionals working for a Midwestern financial services organization. The hierarchical regression results indicated that some dimensions of moral intensity were positively related to PIE, ethical issue recognition, and ethical judgment, and that PIE was associated with increased ethical issue recognition and ethical judgment. The steps of ethical reasoning were also positively interrelated.